The development of undergraduate students\' fanfictional creative writing in English - Placido, Carlos Eduardo de Araujo (2019)
Creative Writing in English (CWE) has not been extensively researched in Brazil. There are few courses about CWE in Brazilian Languages and Literature universities, and even fewer available publications in this area as well (Myers, 2006; Morley, 2007; Blythe and Sweet, 2008; Healey, 2009; Oberholzer, 2014). According to Brazilian Educational Bases and Guideline Law, creativity should be comprehended as one of the main foundations of the Brazilian education, from the primary schooling to the tertiary level. For higher education, this law established the importance of stimulating cultural creation, creative thinking broadening, creative skills honing and cognitive capacities. Nevertheless, very few Brazilian institutions have provided their Languages and Literature undergraduate students with CWE disciplines and/or extracurricular courses focusing on the development of their students\' creative writing The University of São Paulo (USP) is one of these few institutions. For these reasons, a Fanfictional Creative Writing in English (FCW) course was designed and taught at USP by the end of 2016. This course had 5 participants who were all Languages and Literature undergraduate students from USP. The aims of the FCW course and this research were to identify the students\' concepts about creativity, fanfictions and creative writing courses. Along with these identifications, the other aims have been the investigation of the students broadening of these concepts and the development of their fanfictional creative writing. The methodology of this research involved the organization and teaching of the extracurricular Fanfictional Creative Writing in English course. In order to achieve the aims of this research, the extracurricular course was based on the Vygotskian sociocultural theory (Vygotsky, 2004; 2007). The data collected indicated that the Fanfictional Creative Writing in English students developed their creativity, self-expression, imagination (Vygotsky, 2004; 2007), conceptual thinking (Lantolf, 2015), self-regulation as well as agency (Wertsch, 1998).